Protocol: Effects of midazolam on postoperative delirium in elderly patients undergoing spinal surgery: A randomized, double-blind, placebo-controlled non-inferiority trial - Chaoxu Sheng; Miao Zhu; Liyong Yuan; Jianlin Wang; Bo Hu; Xiaolu Huang; He Han (PLoS ONE, 2026)
Introduction Postoperative delirium (POD) is a common complication in elderly patients, linked to prolonged hospitalization, increased morbidities, and mortality. Midazolam, a widely used perioperative benzodiazepine, has controversial associations with POD: some studies suggest risks, while others find no significant link, but evidence quality remains low. This trial explores whether midazolam is non-inferior to placebo in POD incidence among elderly spinal surgery patients. Methods and analysis A single-center, randomized, double-blind, placebo-controlled non-inferiority trial at Ningbo No. 6 Hospital, China, enrolling 692 elderly patients undergoing elective spinal surgery under general anesthesia. Exclusions include emergency surgery, long-term preoperative benzodiazepine use, and severe cognitive impairment. Participants are randomized 1:1 to receive midazolam (2 mg) or placebo (saline) during induction, via sealed envelopes. Blinding is maintained except for the preparing nurse. Primary outcome: POD incidence assessed by Evaluation tool: Confusion Assessment Method (CAM) on postoperative days 1–3. Secondary outcomes include POD details, agitation (Richmond scale), pain (NRS), lab indicators, hospital stay, and complications.